Implications of Organizational Justice on Work Motivation in BJA Medan - Ananda, Yola; Nazmah, Nazmah (Universitas Pamulang, 2023)
This study aims to determine the implications of organisational justice on increasing work motivation in BJA Medan employees with the research subject of BJA Medan employees. The approach used in this research is qualitative and quantitative. The technique used to reveal the research variables with semi-structured interviews with employees from various backgrounds and the provision of work motivation measurement tools to determine the level of employee work motivation. The results of the analysis show that there is a consensus among employees that distributive justice is a key factor affecting work motivation. Employees feel motivated when distributive justice, procedural justice, interactional justice are met in balance. In conclusion, this study illustrates the influence of organisational justice on work motivation. Distributive justice, procedural justice, and interactional justice were identified as factors that influence employees' work motivation. The findings provide valuable insights for organisations in designing policies and practices that promote organisational justice, thereby enhancing employee work motivation and overall performance.